Spiritual Public Political Communication: A Case Study of the Neo Protest Movement Led by Phra Phothirak - Sangsumlee, Chutiwan; Katasila, Suriyasai (Journal of Dhamma for Life, 2025)
This research aims to study the patterns, methods, and processes of public political communication employed by Phra Phothirak through the case study of NEO PROTEST - a unique movement that integrates “Dhamma and democracy.” The research adopts a qualitative methodology including in-depth interviews, participant observation, and documentary analysis of Dhamma media and activities conducted by the Santi Asoke movement. The findings indicate that Phra Phothirak’s communication goes beyond transmitting political messages or demands. It reflects moral ideology through speech, behavior, and symbolic practices. The protest space is transformed into a Dhamma zone - a peaceful and disciplined public sphere without confrontation or violence. The audience is not merely passive receivers, but individuals open to internal transformation. Applying Berlo’s SMCR Model, Habermas’s concept of Public Sphere, and New Social Movement theory, the study reveals the ethical-spiritual dimensions of this alternative political movement. The findings suggest practical implications for public policy, civic education, and the promotion of ethical public space in Thai society.